A Social Semiotic Analysis of Tri Hita Karana Representation in the Contemporary Illustrations of Ayu Pitriani - Ni Putu Anggi Pramesti; Sang Made Aditya Putra; I Wayan Tenda Juniarta (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Popular illustration serves as an effective medium for conveying local cultural values to younger audiences. This study aims to explain how Ayu Pitriani’s Tri Hita Karana illustration series represents the three relational pillars, including the connection between humans and the divine, the relationship among individuals, and the interaction between humans and the environment. The study also explores the ideologies embedded in the visual construction of the artworks. A qualitative and interpretative approach was applied using the social semiotic framework of Kress and van Leeuwen to analyze the visual grammar encompassing representational, interactive, and compositional meanings. This analysis was complemented by Barthes’ semiotic theory, which examines three layers of meaning: denotation, connotation, and myth. The data consist of five illustration panels analyzed through close reading. The analytical process included denotative description, visual element coding, mapping of Balinese cultural connotations, and identification of emerging myths. The findings reveal that simple visual strategies, such as the use of pastel colours, youthful characters, and vertical offering compositions, create layered meanings that connect sacredness with everyday life and harmony with conflict. The panel depicting a polluted river presents Tri Hita Karana as an ecological practice, while the land dispute scene highlights harmony as a result of social negotiation. These findings demonstrate the potential of contemporary illustration as a medium for cultural and environmental literacy and as a teaching resource in Visual Communication Design rooted in local wisdom.